Parasitic and fungal agents in Aoutus sp, Alouatta seniculus and Cebus albifrons in the Colombian Caribbean - Echeverri De la Hoz, Daniel Mauricio (2020)
The aim of this work was to determine the prevalence of intestinal parasites and dermatophyte fungi in captive primates (Aoutus sp, Alouatta seniculus and Cebus albifrons) taken to the Centre for Attention Care and Assessment of Wild Fauna and Flora - CAVFFS (Valledupar, Colombia). Faecal sample were analysed, and direct mycological examinations were performed on skin and hair samples from 17 primates that were accepted in CAVFFS between January and May 2018. Entamoeba histolytica (41%), Entamoeba coli (29%), Endolimax nana (24%), Strongyloides sp (18%), Enterobius vermicularis (18%), Ascaris lumbricoides (12%) and Balantidium sp (12%) in faecal samples, as well as fungi of the genera Aspergillus, Rhizopus, Candida and Fusarium in samples of skin or hair were found.